Ethosuximide-loaded alginate/polyethylene oxide 3d-printed scaffolds for epilepsy treatment - ULAĞ, SONGÜL (My University, 2023)
A chronic medical disease known as epilepsy typically causes spontaneous, unprovoked repeated seizures that have an impact on a variety of mental and physical activities. The majority of epilepsy patients can manage their seizures with medical treatment. More than one-third of patients who do not receive adequate benefit from oral antiepileptic drug therapy continue to have seizures. It is considered as a proper option to design local drug release to the focal area of the brain where the seizure occurs in order to reduce side effects of antiepileptic drugs and to increase therapeutic efficacy by providing higher and more effective doses to the seizure focus. This study concentrates on polymer-based implants, which are polymeric devices loaded with AED and designed for implantation at the seizure focus to provide gradual, prolonged release of AED directly into the area of the brain responsible for seizures. Ethosuximide, an antiepileptic drug used in the treatment of absence seizures, was chosen as the active ingredient in this study. With 3D printing, implantable scaffolds consisting of Alginate and polyethylene oxide polymers and containing the active substance ethosuximide were produced. The properties of drug-containing polymeric scaffolds were investigated by SEM analysis, and their chemical and thermal properties were analyzed using DSC and FTIR, respectively. The drug release of the scaffolds was tested in vitro. In this study, human neuroblastoma cell line, SH-SY5Y (CRL-2266™, ATCC) was used for toxicity analysis.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)